Scope and assessment of the insurance for members of voluntary fire brigades provided by local government - Kuligowska, Angelika (Copernican Journal of Finance & Accounting, 2016)
You can get help in immediate vicinity from the emergency services during a fire, flood or other emergency assistance. Lifeguards can be divided into those who perform their duties professionally and those who are volunteers. Keep in mind that emergency services, such as nurses, fire brigade or mountain rescuers put their lives and health for the salvage of one’s wealth or life. Both residents and the authorities should be depend that in their area will be volunteer fire brigade, because they are often the first help. Quick response to the threat may lessen the damage. The aim of the article is to check whether municipalities in Poland provide adequate protection for firefighters, in particular by insurance. The question of whether local authorities provide sufficient protection for volunteer firefighters. As a consequence, it examines the legal basis to impose compulsory insurance firefighters. In the article analyzed the risks faced by different types of firefighter. It turns out that only a part of taking an active in rescue operations. The information collected compared with the insurance contracts concluded by the municipality. The study served insurance documents municipalities in the Kujawsko-Pomorskie districts aleksandrowski, inowrocławski and radziejowski.